Republic of Congo Trade Facilitation Intervention : Trade Facilitation between Congo and Its Neighbors - Addressing the Bottlenecks - World Bank Group (World Bank, Washington, DC, 2017)
Trade facilitation is one of the key engines of growth in an economy. Improving the quality and reliability of the trade facilitation infrastructure and services is a major building block for reducing transaction costs, attracting domestic and foreign investment, and expanding access to economic opportunities. The Government of Congo, Rep. recognizesthat more needs to be done to address existing constraints to intra-regional trade. Indeed, efficient trade facilitation is central to achieving the objectives of Congo’s Vision 2025, whose overarching goal is to transform the country from a lower middle income economy to an upper middle income export-oriented economy. Attaining the country’s vision will require the addressing of at least three key constraints. Firstly, low investment in the development and maintenance ofthe country’s physical infrastructure; secondly, an insufficient and ineffective capacity to deliver therequired transport and port services; and thirdly, a lack of international competitiveness and export diversification. Addressing these constraints will catalyze the development of modern transport infrastructureand services, contributing to a reduction in the cost of doing business and thus increasing the country’scompetitiveness.Several policies and other interventions have been implemented by the Government to address the country’s trade facilitation challenges. Some of these interventions prioritize improving the quality and reliability of transport and port infrastructure and service, whichis critical for reducing transaction costs and attracting investments, contributing to the broader goals of inclusive growth by connecting rural communities toeconomic activities. This report aims to complement these efforts by making two key contributions. Firstly, it identifies thecore trade facilitation bottlenecks facing the country,and explores options for mitigating these challenges. Secondly, it presents an action plan covering both theexpansion of physical infrastructure and the developmentof transport sector structure, regulation, and institutional capacity; distinguishing between the short-and longer-term measures. The action plan is expected to strengthen the strategy for sustainable economic development and for informing dialogue on required reform measures. The report’s recommendations are also expected to support more inclusive growth, and also ensure that said inclusive growth is sustainable. It is hoped that the report’s findings will be used to inform the designand implementation of the measures required to promote trade facilitation.